2020
DOI: 10.1007/s10597-020-00664-x
|View full text |Cite
|
Sign up to set email alerts
|

Depression, Anxiety and Stress Among Indians in Times of Covid-19 Lockdown

Abstract: Covid-19 has caused significant distress around the globe. Apart from the evident physical symptoms in infected cases, it has caused serious damage to public mental health. India, like other countries, implemented a nationwide lockdown to contain and curb the transmission of the virus. The current research is an attempt to explore psychological distress among people residing in India during the lockdown. Four hundred and three participants were asked to complete a questionnaire with questions around symptoms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

45
385
5
20

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 495 publications
(455 citation statements)
references
References 23 publications
45
385
5
20
Order By: Relevance
“…Such gender difference has been reported mostly due to biological component and different coping strategies they have. This nding is in line with studies conducted in Nepal, China, India and Italy 12,14,16 . In this study, both anxiety and depression were found to be associated with marital status.…”
Section: Discussionsupporting
confidence: 91%
“…Such gender difference has been reported mostly due to biological component and different coping strategies they have. This nding is in line with studies conducted in Nepal, China, India and Italy 12,14,16 . In this study, both anxiety and depression were found to be associated with marital status.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, female participants had a higher prevalence of both anxiety (39.5% vs 11.6%, p<0.01) and depression (18.6% vs 9.3%, p=0.351). This nding is in line with studies conducted in Nepal, China, India and Italy 10,12,14 .…”
Section: Discussionsupporting
confidence: 91%
“… 14 Factorial Validity of the Urdu Version of the Obsession With COVID-19 Scale: Preliminary Investigation Using a University Sample in Pakistan ( Ashraf, Lee, & Elizabeth Crunk, 2020 ) University students and teachers; n = 240; Online survey; Cross-sectional study Psychometric properties The Urdu version of the Obsession with COVID-19 Scale (OCS) showed weak positive correlations with the total scale and social dysfunction and self-confidence subscales of the General Heath Questionnaire (GHQ-12) and no correlation with the depression and anxiety subscale. 15 Depression, Anxiety and Stress Among Indians in Times of COVID-19 Lockdown ( Rehman et al, 2020 ) General population; n = 403; Online survey; Cross-sectional study Depression, anxiety, stress Not having sufficient supplies during the lockdown was associated with being more adversely affected by COVID-19. Socioeconomic status was negatively correlated with stress, anxiety, and depression.…”
Section: Resultsmentioning
confidence: 99%